ANALISIS PENGELOLAAN DANA TALANGAN KBIHU SAFARA QOLBY PROBOLINGGO - Siti Wasila; Siti Aisyah; Nor Fijah Amaliah; Rohana; Ernawati; Reza Hilmy Luayyin (Wasīlah: Journal Of Sharia Sciences, 2025)
This study aims to analyze the fund management system in the Hajj and Umrah services carried out by KBIHU Safara Qolbi and PT Safara Layanan Utama in Probolinggo Regency. The focus of the study is on how pilgrim funds, whether paid in cash or through a bridging or credit system, are managed with the principles of transparency, accountability, and customer satisfaction-based service. The method used is descriptive qualitative with a case study approach through in-depth interviews, observations, and direct documentation in the field. The results of the study indicate that fund management at Safara is carried out in an orderly and safe manner, with a clear distinction between Hajj funds directly deposited into government banks and Umrah funds managed internally by the institution. The bridging system is facilitated through collaboration with a trusted cooperative, and is carried out with disciplined procedures, including verification of the eligibility of prospective pilgrims. Safara also limits the quota of pilgrims to ensure quality of service and directly accompanies each departure. No misappropriation or illegal investment practices of pilgrim funds were found, which makes this management model worthy of emulation by similar institutions.